BERTRAND MATE OF TIMELIKE BIHARMONIC GENERAL HELICES IN THE LORENTZIAN E(1, 1) - Korpinar, Talat; Turhan, Essin (Accad Peloritana Pericolanti, 2012)
In this paper we study a Bertrand mate of timelike biharmonic general helices in the Lorentzian group of rigid motions E(1, 1). Finally, we find out their explicit parametric equations.
Keywords: Curves